Wheel-Running Facilitates Phase Advances in Locomotor and Peripheral Circadian Rhythm in Social Jet Lag Model Mice - Oneda, Satoshi; Cao, Siyuan; Haraguchi, Atsushi; Sasaki, Hiroyuki; Shibata, Shigenobu (Frontiers in Physiology, 2022)
The circadian clock maintains our health by controlling physiological functions. Social jet lag is one factor that can disrupt the body clock. This is caused by the difference in sleeping hours between weekdays when we live according to social time and holidays when we live according to our body clock. The body clock can be altered by exercise, nutrition, and stress, and several studies have reported that these factors can be used to improve a disturbed body clock. Here we focused on exercise and examined whether continuous wheel-running could improve the disordered body clock in a mouse model that mimics social jet lag. The results showed that the wheel-running exercise group showed faster synchronization of the onset of activities on weekdays which had been delayed by social jet lag and the results were even more pronounced in the high-fat diet feeding condition. Also, when the expression rhythms of the clock genes were examined, they experienced a sudden time shift in the advance light condition or social jet lag condition, it was found that the wheel-running group had a higher ability to adapt to the advance direction. Thus, it is possible that the effective inclusion of exercise in human, especially those who eat high-fat foods, life can improve the disordered body clock in terms of social jet lag.